2022
DOI: 10.2196/33489
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Digital Health Technologies in Knee Osteoarthritis: Narrative Review

Abstract: Background With the increasing adoption of high-speed internet and mobile technologies by older adults, digital health is a promising modality to enhance clinical care for people with knee osteoarthritis (KOA), including those with knee replacement (KR). Objective This study aimed to summarize the current use, cost-effectiveness, and patient and clinician perspectives of digital health for intervention delivery in KOA and KR. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 116 publications
0
9
0
Order By: Relevance
“…Digital therapeutics, including smartphone apps, have emerged as an accessible solution to address these barriers with the potential to facilitate better patient-provider interactions and lead to more personalized care [ 7 , 10 , 11 ]. These interventions have shown efficacy in promoting physical activity and improving patients’ pain, function, and quality of life [ 7 , 12 , 13 ]. A major requisite to a digital intervention’s success is adherence [ 14 , 15 ], defined as the extent to which a person’s behaviour matches agreed recommendations [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital therapeutics, including smartphone apps, have emerged as an accessible solution to address these barriers with the potential to facilitate better patient-provider interactions and lead to more personalized care [ 7 , 10 , 11 ]. These interventions have shown efficacy in promoting physical activity and improving patients’ pain, function, and quality of life [ 7 , 12 , 13 ]. A major requisite to a digital intervention’s success is adherence [ 14 , 15 ], defined as the extent to which a person’s behaviour matches agreed recommendations [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, implementation of these recommendations in clinical practice is suboptimal, with two recent systematic reviews reporting that only one in three persons with OA receives appropriate non-pharmacological care according to the guidelines [5,6]. Lack of knowledge about treatment approaches and guidelines by healthcare providers and patients, limited provision of these treatments, and constraints related to access, time, and costs have been identified as major barriers to implementing these recommendations in clinical practice [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This trial will contribute with knowledge regarding an innovative approach to OA management, through the integration of a digital intervention strategy. Previous studies have found the use of digital interventions in OA care and musculoskeletal physiotherapy to be potentially as effective as standard treatment 25 40. If deemed to be non-inferior, further integration of digital exercise programmes in the treatment of patients with OA could fulfil the requirement of a personalised treatment approach, creating an option for greater empowerment of the patient 41.…”
Section: Discussionmentioning
confidence: 99%
“…Increased knowledge and sound trials evaluating the use of digital interventions are sought for in musculoskeletal conditions 40 45. This trial will add to the current knowledge on effectiveness of digital interventions and may provide knowledge that can be used in improving accessibility and quality in OA care.…”
Section: Discussionmentioning
confidence: 99%
“…104 However, some also valued the "undivided communication" offered via phone-based interventions. 107 One review noted that patients reported more positive experiences with both phone and video consultations being used together. 57 2.…”
Section: Communication Systemsmentioning
confidence: 99%